Towards a Russia of the regions - Nicholson, Martin; International Institute for Strategic Studies (Oxford [England] : Oxford University Press for the International Institute for Strategic Studies, 1999)
Russia's state system has changed significantly since 1991, but the question of how the country should be governed has not been answered. Russia's constitutional framework is weak and inherently flawed, and the balance of political and economic power between the centre and the regions is ill-defined. In the absence of a firm constitutional settlement, regional elites have consolidated power, restricting the growth of local democracy and frustrating attempts at grass-roots economic reform. Establishing an effective and regulated relationship between the federal centre and the regions requires greater decentralisation, but devolution need not threaten Russia's integrity if it is transparent and based on a greater respect for the rule of law.
The making of today's Russia -- The economic dimension -- The political dimension -- The strategic dimension.
Includes bibliographical references.
Keywords: Since 1991; Regionalism -- Russia (Federation); Federal government -- Russia (Federation)